Surgical Correction of Kyphosis in Patients With Camptocormia Associated With Parkinson’s Disease: A Case Report and Review of the Literature - Mei, Guo-long; Wei, Hui-ting; Ma, Yue-rong; Wan, Dun (Frontiers in Surgery, 2022)
Background Camptocormia is a postural deformity that is characterized by a markedly flexed lumbar spine, with symptoms that worsen with walking and standing. Here, we report a case of camptocormia associated with Parkinson’s disease. Case description A 70-year-old man with a 7-year history of Parkinson’s disease presented with a fall injury that caused lower back pain for 3 months and was aggravated for 2 months. He had been diagnosed with a compression fracture after the fall and had undergone percutaneous kyphoplasty at a local hospital. MRI showed non-union of the L1 vertebra and compression fracture of L2. The patient underwent posterior osteotomy, canal decompression, and internal fixation of the T10-L3 intervertebral plate with bone graft fusion. Postoperative examination showed that the lumbar lordosis was corrected and sensation was restored in both lower extremities. However, after 1 month, the fixation was loosened and a correction surgery was performed at our hospital. At the most recent follow-up at 1.5 years, the patient was found to be in good general health and did not complain of lower back discomfort. He was also actively exercising according to the rehabilitation regimen and had resumed social life. Conclusion This is a rare case of camptocormia in a Parkinson’s patient that highlights the need for careful evaluation of whether internal spinal fixation surgery is beneficial in such patients.